THE PROFILE OF LEARNING ENVIRONMENT AND COGNITIVE ABILITY IN ENVIRONEMNTAL POLLUTION TOPICS OF STUDENTS' AT SEKOLAH INDONESIA KUALA LUMPUR - Hanifah Mulyani (Jurnal Pengajaran MIPA, 2020)
This research aims to analyze the learning environment and cognitive ability of students who experience discussion in learning about environmental pollution at Sekolah Indonesia Kuala Lumpur (SIKL). Furthermore, this research is purposed to analyze the factors influencing students’ discussion process at SIKL. This research uses a descriptive method to describe the current condition of discussion followed by 24 students in 7 grade as the sample. The data in this research is gained through pre-test and post-test scores, questionnaires based on CLES, and students’ interviews. According to this research, the learning environment created through discussion activities affects students’ cognitive ability at SIKL. Learning activities are affected by factors such as students’ prior knowledge, their learning style students, conformity, gender differences, students’ intelligence, and students’ interests. Moreover, this research suggests that teachers who apply the discussion method consider the above factors. The teacher has to be eager to pack discussion becomes more interesting and valuable to make students feel a joyful atmosphere in learning.